POST-AMI: A STUDY OF PLANNED OUTPATIENT ANGIOGRAPHY AFTER SUCCESSFUL THROMBOLYSIS IN STEMI PATIENTS. - Khan, Zia Ullah; Afsar, Rukhshanda; Khan, Mohammad Imran; Shams, Saad; Ahmad, Aftab; Iqbal, Mohsin (Journal of Ayub Medical College Abbottabad, 2026)
BACKGROUND: The current recommendations regarding STEMI patients who are treated with thrombolysis in non-PCI centers are to transfer such patients to a facility capable of angiography as soon as possible. However, many emerging PCI-capable centers thrombolyse patients in acute settings because they have not yet achieved primary PCI capability. Could successfully thrombolysed patients undergo nonurgent angiography in such settings without the risk of major complications? In the setting of limited resources, where urgent angiographies could be reserved for rescue or other urgent indications, demonstrating the safety of non-urgent outpatient angiography in successfully thrombolysed patients would be useful. METHODS: One hundred consecutive patients presenting within 12 hours of symptoms for their first STEMI and meeting our inclusion criteria were given 1.5 MU of Streptokinase and guideline-directed medical treatment. Successfully thrombolysed patients were scheduled to undergo angiography within 72 hours of discharge. The primary outcome was event-free survival up to angiography or unscheduled admissions for recurrent angina or re-infarction or death while waiting for angiography. RESULTS: All patients were accounted for. About 80% of patients were males. ST-segment resolution of ≥70% was associated with TIMI III flow at angiography in 90% of patients. TIMI 0 was found in only 8%. All patients survived to have their outpatient angiographies within 72 hours. There were no unscheduled admissions for recurrent angina or re-infarction while waiting for angiography. CONCLUSION: ST-segment resolution of ≥70% is a sensitive marker of good short-term prognosis and a patent infarct-related artery on angiography. Routine outpatient angiography within 72 hours of discharge can be safely undertaken in patients who show resolution of chest pain with 70% or more ST-segment resolution at 90 minutes post-thrombolysis.